SCREENING AND IDENTIFICATION OF POTENTIAL BIOSURFACTANT PRODUCING MICROORGANISMS ISOLATED FROM OIL CONTAMINATED SOILS - P.SAMINATHAN; P.RAJENDRAN (International Journal of Pharma and Bio Sciences, 2014)
Biosurfactant are surface active compounds produced by microorganisms. These molecules reduce surface tension between aqueous solutions and hydrocarbon mixtures. Hundred hydrocarbon saturated soil samples were collected from thirty different areas in Chennai, TamilNadu, India. Seventy two bacterial strains were isolated and cultured by enriching carbon (Glycerol) source. Each culture medium was screening to confirm the ability of biosurfactant production. These were conducted using surface tension and emulsification activity methods. The result reveals that fifty four strains of bacteria showed surface tension in the range between 0.026Nm-1 to 0.072Nm-1. The emulsifying capacity evaluated by the E24 emulsification index range from 36-85% EA. Among 54 isolates, 9 isolates displayed highest activity after detection with emulsification index method. They were identified for potent biosurfactant production. These were conducted using series of screening methods.